The Effect of Person Organization Fit and Work Motivation on Employee Performance With Job Satisfaction as an Intervening Variable - Santi Wilasari; Lie Liana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Competition in the world of banking, especially in people's economic banks, requires the development of quality human resources to increase employee capabilities and employee contributions outside formal roles. Employees' ability to balance professional, personal life, and spiritual intelligence is a factor in fostering good corporate behavior. The main purpose of this research is to find out whether person-organization fit and work motivation influence performance with satisfaction as a mediating factor, in the banking context, especially the People's Economic Bank. This research took the population at PT BPR Artha Mranggenjaya Demak, which has 87 employees. These criteria were chosen to ensure respondents have sufficient experience and personal stability to reflect the company's suitability for improving performance, as well as providing a sense of employee satisfaction. The research results state that person-organization fit and work motivation influence employee performance and cannot be mediated by job satisfaction. These findings show that job satisfaction is not an important factor for human resource development in companies, but company management needs to pay attention to employees so that they are satisfied with what has been assigned by the company.